1994
DOI: 10.1128/mcb.14.6.3604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a null mutation of the insulin-like growth factor I receptor gene on growth and transformation of mouse embryo fibroblasts.

Abstract: Fibroblast cell lines, designated R-and W cells, were generated, respectively, from mouse embryos homozygous for a targeted disruption of the Igflr gene, encoding the type 1 insulin-like growth factor receptor, and from their wild-type littermates. W cells grow normally in serum-free medium supplemented with various combinations of purified growth factors, while pre-and postcrisis R-cells cannot grow, as they are arrested before entering the S phase. R-cells are able to grow in 10% serum, albeit more slowly th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
366
1
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(394 citation statements)
references
References 54 publications
25
366
1
2
Order By: Relevance
“…One such pathway is centered on IGF-1 ligation to its cognate membrane receptor, which has been shown to increase survivin expression in prostate (Zhang et al, 2005), myeloma (Stromberg et al, 2006) and liver (Hopfner et al, 2006) tumor cell types, even though the underlying mechanism(s) of this response had remained elusive. As now reported here, this pathway depends on IGF-IR transforming potential (Sell et al, 1994), does not involve changes in cell cycle distribution and is not associated with de novo survivin promoter activity or increased survivin protein stability. Conversely, IGF-1 modulates survivin levels by favoring stabilization and translation of a survivin mRNA pool through activation of the mTOR pathway.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…One such pathway is centered on IGF-1 ligation to its cognate membrane receptor, which has been shown to increase survivin expression in prostate (Zhang et al, 2005), myeloma (Stromberg et al, 2006) and liver (Hopfner et al, 2006) tumor cell types, even though the underlying mechanism(s) of this response had remained elusive. As now reported here, this pathway depends on IGF-IR transforming potential (Sell et al, 1994), does not involve changes in cell cycle distribution and is not associated with de novo survivin promoter activity or increased survivin protein stability. Conversely, IGF-1 modulates survivin levels by favoring stabilization and translation of a survivin mRNA pool through activation of the mTOR pathway.…”
Section: Discussionsupporting
confidence: 65%
“…When incubation reactions were prolonged to 48 h, IGF-1 and rapamycin were replaced daily in fresh medium. MEF from IGF-IR null mice (RÀ), or MEF transfected with human WT IGF-IR were cultured as described (Sell et al, 1994). RÀ cells were transduced with retroviral particles expressing IGF-IR mutants GR35 and GR48, and stable cell lines were selected using geneticin (1 mg/ ml).…”
Section: Cell Culture Conditionsmentioning
confidence: 99%
“…Evidence for the involvement of IGF-1 signaling in tumorigenesis comes from several distinct observations as follows: (i) tumors originating from breast (Yee et al, 1989), colon (Tricoli et al, 1986), and lung (Minuto et al, 1986) in humans, and skin in mouse (Rho et al, 1996) have been shown to overexpress either IGF-1, IGF-1r or both; (ii) overexpression of IGF-1r confers ligand dependent transformation in cultured cells (Kaleko et al, 1990); (iii) IGF-1 expression is elevated in cells carrying an activated p21 Ha-ras (Dawson et al, 1995); (iv) IGF-1 has been shown to induce the expression of other mitogenic growth factors (Vardy et al, 1995); and (v) ®broblasts obtained from IGF-1r null mice were highly resistant to transformation by SV40-T antigen, activated Ha-ras, or a combination of both, while re-introduction of wild-type IGF-1r again conferred susceptibility to transformation (Sell et al, 1993 andSell et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The crucial finding that clearly pointed out the major role played by the IGF-IR in cellular transformation was the demonstration that knock-out mouse embryo cells for this receptor are refractory to transformation by viruses, oncogenes and by other overexpressed growth factors receptors; each of these conditions that readily transform cells. 20,21 Relevant to the role of IGF-IR in tumorigenesis is its anti-apoptotic function, IGF-IR has been shown to protect tumor cells from apoptosis in vivo. 22 Overexpression of IGF-IR protects cells from UV irradiation-, cytokine-and gamma radiation-induced apoptosis.…”
mentioning
confidence: 99%